Azoospermia in Sulaimani - Rasheed, Aso Omar; Abed, Sabah (Sulaimani Journal for Pure and Applied Sciences, 2004)
One hundred patieruts v,ith azoospertnia were diagnosed, investigcted and treated accordingly, this is a praspective sfitdy carried on patients presented with infertilitlt, abnorwal genitalia, accidental azoospermia, from July 2001 to htne 2442. Design; clinical diagnosis was made hy history, physical examiaation, and serial seminal fiuid examination, testicular biopsy examined by consultant pathologist end horuonal assay.Obiective; to identify the etiology of the ezoospermiu and to determine their future outcome.Resultg azoospermia regarded as one af the dfficwl.t conditian Jbr the treotment as most of the cases are due to primary testicular failure . Co*clusion; small testis with higlt FSH need no farther assessmet* better ta explain the conditionfor them .
Keywords: Seminal fluid analysis; Hypogonadism; Gonadotropin